Effects of Hypoxia and Acidosis on Cardiac Electrophysiology and Hemodynamics. Is NHE-Inhibition by Cariporide Still Advantageous? - Salameh, Aida; Zöbisch, Helena; Schröder, Bianca; Vigelahn, Jonas; Jahn, Mandy; Abraham, Getu; Seeger, Johannes; Dähnert, Ingo; Dhein, Stefan (Frontiers in Physiology, 2020)
Hypoxia often leads to severe cardiac malfunctions. It is assumed that intracellular calcium overload is -inter alia- responsible for left ventricular (LV) deterioration. Inhibition of the sodium-proton exchanger (NHE), which finally inhibits/slows calcium overload, may ameliorate cardiac function. Our aim was to evaluate cariporide, an inhibitor of NHE1 in a Langendorff-perfused heart model. To discriminate a potentially different impact of extracellular acidosis and hypoxia we examined 48 Chinchilla Bastard rabbits divided into 8 experimental groups: control group (pH=7.4, O2=100%) without and with cariporide (1µM), acidosis group (pH=7.0, O2=100%) without and with cariporide (1µM), hypoxia group (pH=7.4, O2=40%) without or with cariporide (1µM) and hypoxia+acidosis group (pH=7.0, O2=40%) without or with cariporide (1µM). Hearts were subjected to acidotic/hypoxic conditions for 90minutes followed by 60minutes of reperfusion. Hypoxia and hypoxia+acidosis led to a severe deterioration of LV function with a decrease in LV pressure by about 70% and an increase of end-diastolic pressure from 6.7+0.6 to 36.8+5.4 (hypoxia) or from 7.0+0.2 to 18.6+4.1 (hypoxia+acidosis). Moreover, maximum contraction velocity decreased from about 1800mmHg/s to 600mmHg/s during hypoxia+acidosis and maximum relaxation velocity deteriorated from -1500mmHg/s to about -600mmHg/s. During reperfusion hearts subjected to hypoxia+acidosis recovered faster than hearts subjected to hypoxia alone, reaching control levels after 5min of reperfusion. Electrophysiologic analysis revealed an 1.2fold increase in both dispersion of activation-recovery interval and in total activation time in the hypoxia+acidosis group. Cariporide application significantly improved LV hemodynamics and electrophysiology in the hypoxia group but not in the group subjected to hypoxia+acidosis. Immunohistologic analysis of cardiac specimen revealed a significant increase of factors involved in hypoxia/reperfusion injury like nitrotyrosine and poly-ADP-ribose as well as apoptosis-inducing factors like AIF or cleaved-caspase 3 in LV after hypoxia+acidosis. ATP was reduced by hypoxia but not by acidosis. Again, cariporide mitigated these processes only in the hypoxia alone group, but not in the group with additional acidosis. Acidosis without hypoxia only marginally disturbed LV function and electrophysiology, and was not affected by cariporide. Thus, our study demonstrated that several detrimental effects of hypoxia were mitigated or abrogated by acidosis and that NHE-inhibition improved only hypoxia-induced cardiac dysfunction.